Updates in school-based asthma management. Issue 2 (24th April 2023) - Lowe, Ashley A.; Onge, Ina St; Trivedi, Michelle
Abstract : Purpose of review: School-based asthma management is an important component of pediatric asthma care that has the potential to provide more universal evidence-based asthma care to children and mitigate asthma-related health inequities. The purpose of this review is to highlight relevant developments in school-based asthma management over the past 2 years. Recent findings: There have been considerable recent scientific advances in school-based asthma management including robust clinical trials of environmental interventions in the classroom setting, school-nurse led interventions, stock albuterol policy changes, school-based telemedicine approaches and innovative methods to engage community stakeholders in research that have pushed the frontiers of school-based asthma care. Summary: Recent scientific work in school-based asthma management demonstrates the potential power of schools in providing access to guideline-based asthma care for all children with asthma and in improving their health outcomes. Future work should focus on the evaluation of methods to promote the adoption of school-based asthma management strategies in real-world practice and support evidence-based policy change and strategic partnerships to improve asthma health outcomes and produce meaningful public health impact for diverse children and families.